Assessing the Impact of Immersive Technologies on Media Engagement and Communication in Nigeria - Ja'afaru, Sharifatu Gago; Anagu, Emmanuel John (Department of Communications, Universitas Islam Indonesia, 2025)
This study examines the impact of immersive technologies on media engagement and communication in the Nigerian media environment. It aims to assess the current state of immersive technologies in the Nigerian media industry, identifies existing barriers and knowledge gaps, and explores how the adoption of immersive tools enhances media content creation and operational practices. Applying, Uses and Gratification Theory, the research illustrates how audience members engage with media contents to satisfy certain needs. A survey method provides a thorough understanding of the immersive technologies’ effects on media engagement and communication in the Nigerian media space. A multiple regression analysis was carried out to assess the extent to which UGT-based gratification needs predict the use of immersive technology. The model produced an R² of 0.485, indicating that the five gratification constructs accounted for 48.5% of the variance in immersive technology use. The model’s correlation coefficient (R) was 0.696, implying a robust positive relationship between users’ needs and their engagement with immersive media. The study concluded that gratification-driven motivations promote the adoption and use of immersive technologies within media organisations in Nigeria. The results illustrate that the incorporation of immersive media, strengthened by innovative strategies and technological frameworks, significantly enhance content delivery, audience engagement, and internal collaboration. Though the future of immersive technology and its adoption in the Nigerian media space looks promising, its potential to thrive is highly dependent on how the industry tackles user experience concerns. Consequently, positioning immersive platforms should be positioned as vital assets for the advancement of media organisations in Nigeria.